Expression of different vascular endothelial markers in prostate cancer and BPH tissue: an immunohistochemical and clinical evaluation - Trojan, Lutz; Thomas, Daniel; Friedrich, Dorothee; Grobholz, Rainer; Knoll, Thomas; Alken, Peter; Michel, Maurice Stephan (Urologic oncology, 2004)
Background: The microvessel density (MVD) is often used as a quantitative parameter for angiogenesis. The aim of this study was to evaluate the three most commonly used endothelial markers of microvessels, CD31, CD34 and vWF, in benign and malignant prostatic tissue. Materials and Methods: Fifteen benign hyperplastic prostate and 54 prostate cancer specimens were immunohistochemically stained for CD31/CD34/vWF. The MVD obtained by each marker was quantified by a vessel count in standardized grids within the area of maximum angiogenesis. The data on MVD was interrelated and compared to tumor staging, grading and clinical follow-up. Results: A significant correlation of the CD31/CD34/vWF-MVD data was observed in BPH tissue, but not in PCa. In PCa, the most sensitive marker for newly derived blood vessels was CD34. While CD34-MVD demonstrated a significant association with tumor grading and PSA follow-up, CD31- or vWF-MVD did not. Conclusion: CD34 is a suitable marker for the immunohistochemical visualization of microvessels in benign and malignant prostate tissue.